La machine à vapeur dans l’aérostation au XIXe siècle - Molveau, Jean (Comptes Rendus. Mécanique)
The steam engine became widely used in all sectors in the $19^{\rm th}$ century. But as far as aerostation was concerned, it was the prerogative of one and only one person, Henri Giffard. Since the advent of balloons in 1783, countless researchers had been thinking, without success, of making airships dirigible. The first credible attempt, in 1852, was made by Henri Giffard, who used a steam engine under the envelope of his elongated balloon inflated with hydrogen... It was the first motorised aircraft in the history of mankind!A few years later, he developed a whole captive balloon system, also powered by a steam engine, a jewel of technology that was one of the main attractions at the Paris International Exhibition in 1878, the Grand ballon captif de la cour des Tuileries. The mechanical principles of this gas-powered balloon are still in use today.